Direct composite veneer to treat primary teeth with sequela of dental trauma: a case report (Revista da Faculdade de Odontologia - UPF, 2012)
Introduction: Tooth discoloration can be one of the main reasons for parents to seek treatment after dental trauma. When this sequela occurs with no other clinical or radiographic symptoms, a conservative approach is recommended. However, when such alterations can compromise the patient’s esthetics and his/her interaction in a social environment, an esthetic treatment may be required. Case report: Here we report the esthetic rehabilitation of a primary maxillary left central incisor presenting coronal darkening in a 5-year-old girl that had been monitored clinically and radiographically due to dental trauma in the maxillary anterior teeth since she was 1 year old. Because of the esthetic complaint, a direct composite resin veneer was performed. Final considerations: After the treatment, a good esthetic result was achieved making the patient and her parents pleased. The esthetic improvement was maintained at the six-month follow-up with no negative impact on the child’s social life.